(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2015)
Background: This paper discusses the sustainable wildlife tourism with specific reference to resorts/hotels in and around Corbett National Park, Uttarakhand. Methods: This study is a part of detailed survey of the park and elaborates the eco-friendliness of these resorts/hotels. 69 (95.8%) resorts/hotels responded in the study. Results: It was observed that only 24.6% resorts/hotels have eco-friendly building, 27.5% have energy management system, 5.7% have water recycling, 14.4% use recycled materials, 37.6% train their staff for eco- friendliness and 27.5% resorts/ hotels have written guidelines for the guests.